Eco-friendly Industrial wastewater treatment: Potential of mesophilic bacterium, Pseudomonas putida (ATCC 49128) for hydrogen sulfide oxidation - Ahmad, Mani Malam; Mohd Azoddein, Abd. Aziz; Jami, Mohammed Saedi (Open Science Publishers LLP, 2018)
The effectiveness and environmental friendliness of biological sulfide oxidation have endeared it to many researchers, mainly for its potential to offer the best alternative for the evacuation of various forms of sulfide. The present study was conducted to assess the potential of gammaproteobacteria, Pseudomonas putida (ATCC 49128), to biodegrade sulfide significantly in a suspended medium of batch reactor type. Sulfide oxidation efficiency was measured spectrophotometrically under defined operational conditions of temperature, agitation, aeration, and influent sulfide concentrations. Sulfide reduction rates were observed at three disproportionate sulfide concentrations of 100 ppm S2− L−1 d−1, 300 ppm S2− L−1 d−1, and 500 ppm S2− L−1 d−1. The simple statistical analysis was employed in the interpretation of the data and presented graphically. The results indicated that it was possible to realize sulfide removal efficiency of 45–70% within the first 6 h of start-up and 96–100% in 24 h period. On the other hand, the corresponding exponential cell growth recorded was 3.91, 3.80, and 3.61 in 100 ppm, 300 ppm, and 500 ppm, respectively. This also translates to cell biomass synthesis (cell dry weight) of 0.61 g/L, 0.58 g/L, and 0.50 g/L in 100, 500, and 300 ppm, respectively. In conclusion, it can be deduced that this inoculum can utilize different sulfide concentration for its growth and biosynthesis and thus can be employed to treat sulfide contaminated wastewater in a suspended growth form.